Pengaruh Kecerdasan Emosional terhadap Perilaku Prososial Siswa - Artuti Adeani Putri (Universitas PGRI SUMATERA BARAT, 2020)
ABSTRACT This research is motivated by the phenomenon of the lack of prosocial behavior in students such as not caring when their friends are: sick, have no money, there are students who do not want to study, there are students who do not want to provide support to their friends who excel. The above phenomenon is influenced by the level of intelligence of students. The purpose of this research is to describe; (1) students' emotional intelligence, (2) students' prosocial behavior, and (3) examines the effect of students' emotional intelligence on students' prosocial behavior. This type of research is descriptive quantitative. The population in this study were students of class IX State Junior High School 12 Padang totaling 280 people. The research sample was taken using a simple random sampling formula so that the sample obtained was 74 people. Collecting data using questionnaires, data analysis using descriptive statistics with proportions and simple linear regression techniques. The findings of this study are: (1) students' emotional intelligence is in a fairly high category, (2) students' prosocial behavior is in a fairly high category. and (3) There is a significant and positive contribution between emotional intelligence on students' prosocial behavior. Keyword : emotional, intelligence, prosocial, behavior, students ABSTRAKPenelitian ini dilatarbelakangi oleh fenomena kurangnya perilaku prososial pada siswa seperti tidak peduli ketika temannya: sedang sakit, tidak punya uang, ada ada siswa yang tidak mau belajar berkelompok, ada siswa yang tidak mau memberikan dukungan kepada temannya yang berprestasi. Fenomena di atas diduga dipengaruhi oleh tingkat kecerdasan peserta didik. Tujuan dari penelitian ini adalah untuk mendeskripsikan; (1) Kecerdasan emosional siswa, (2) perilaku prososial siswa, dan (3) menguji pengaruh kecerdasan emosional siswa terhadap perilaku prososial siswa. Jenis penelitian ini adalah deskriptif kuantitatif. Populasi dalam penelitian ini adalah siswa kelas IX Sekolah Menengah Pertama Negeri 12 Padang yang berjumlah 280 orang. Sampel penelitian diambil dengan menggunakan rumus simple random sampling sehingga sampel berjumlah 74 orang. Pengumpulan data menggunakan angket, analisis data menggunakan statistik deskriptif dengan teknik persentase dan regresi linier sederhana. Temuan penelitian ini adalah: (1) Kecerdasan emosional siswa berada pada kategori cukup tinggi, (2) Perilaku prososial siswa berada pada kategori cukup tinggi. dan (3) Terdapat kontribusi yang signifikan dan positif antara kecerdasan emosional terhadap perilaku prososial siswa. Kata Kunci : Kecerdasan, emosional, perilaku, prososial, siswa